Earthquake Hazard Preparedness in Special Education: Case Studies of Special Needs Schools in Bantul, Indonesia - Hadyyuwono, Lathief Viana Saryhaque; Ruslanjari , Dina; Fathani, Teuku Faisal (Universitas Ahmad Dahlan, 2025)
Special needs school (Sekolah Luar Biasa or SLB) has a higher level of vulnerability compared to a regular school, due to the condition of their students, who are children with special needs. This study analyzes the physical condition and disaster management efforts of SLB Dharma Bhakti Piyungan and SLB Negeri 1 Bantul, Indonesia. Besides, this study also analyzes education, prevention, and disaster risk reduction efforts at those special schools. The mixed methods used in this study are the quantitative and qualitative approaches. Quantitative primary data related to the physical condition of school buildings was obtained from field survey results. In contrast, primary data on disaster management and education, prevention, and disaster risk reduction efforts were obtained from in-depth interviews with triangulation of sources. The data analysis technique used for quantitative data is analysis using rapid visual screening sheets (RVS), FEMA P-154 Level 1 SLB Building. The vulnerability value of buildings in SLB Dharma Bhakti Piyungan was calculated to be 42.85%, falling into the medium-high category and having a high likelihood of suffering earthquake-related damage. In contrast, the vulnerability value of buildings in SLB Negeri 1 Bantul was calculated to be 30.27%, falling into the moderate category and having a low likelihood of suffering earthquake-related damage. Then, SLB Dharma Bhakti Piyungan meets 6 of the 21 indicators for achieving the disaster management pillars, whereas SLB Negeri 1 Bantul meets 16. SLB Dharma Bhakti Piyungan meets four indicators in the disaster risk reduction and prevention education pillar, while SLB Negeri 1 Bantul meets 22.